The level of STEM knowledge, skills, and values among the students of bachelor’s degree of education in geography - Sumayyah Aimi Mohd Najib; Hanifah Mahat; Nur Hidayah Baharudin (International Journal of Evaluation and Research in Education (IJERE), 2020)
The demand for individuals with educational background in Science, Technology, Engineering and Mathematics (STEM) fields has been rapidly growing. This paper presents the level of STEM education knowledge, skills and values among the students of Bachelor’s Degree of Education (B.Ed.) in Geography at Universiti Pendidikan Sultan Idris. Research on STEM education study in geography involves assessing the STEM knowledge, skills and values. This article reports the findings from the survey conducted on 400 students of ISMP in Geography in the first to the eighth semester in 2018. The research instrument involves variables such as knowledge, skills and value. The items for each variable were constructed and modified based on the STEM implementation guide set by the Ministry of Education Malaysia and the Academy of Sciences Malaysia, and validated by the experts. Descriptive analysis was selected to evaluate the level of STEM knowledge, skills and values among the students. The findings show that the students indeed possess high level of STEM knowledge, skills and values. Overall, this study is important to examine the variables that influence the development in Geography and STEM. In a nutshell, this study will help the departments and faculties to further improve the development in Geography field at both national and international levels.